Pengaruh Model Pembelajaran Kooperatif Tipe Make A Match Bermuatan Literasi Sains terhadap Kompetensi Belajar Peserta Didik - Febi Oktavani; Syamsurizal Syamsurizal; Rahmawati Darussyamsu; Ganda Hijrah Selaras (Universitas Negeri Padang, 2020)
Learning problems at Payakumbuh 1 Junior High School are learning models that are less varied, and low learning competencies of students from aspects of knowledge, attitudes and skills. Efforts that can be made are applying the cooperative learning model type make a match with scientific literacy on the material of global warming at Payakumbuh 1 Public Middle School. The aim of the study was to determine the positive effect of the cooperative learning model type make a match with scientific literacy on the learning competencies of students in the subject of global warming at Payakumbuh 1 Junior High School. This type of research is a quasi-experimental study with a randomized control group posttest only design study design. The study population was all class VII Payakumbuh 1 Junior High School registered in the 2018/2019 school year totaling nine classes. Sampling was done using purposive sampling technique, which was selected class VII.4 as the experimental class and class VII.3 as the control class. The instruments used were in the form of posttest questions for knowledge competencies, observation sheets for attitude and skills competencies. The research hypothesis was tested using the t-test. Based on the results of the study using the t-test it can be concluded that the knowledge competencies of the students are tcounts of 0,05> t table1,66, and in the skills competency of tcounts of >60> 1.66 t table. In attitude competency, the experimental class was 86% with a very good category while the control class was 73% with sufficient categories. This shows that the hypothesis is accepted in the competence of knowledge, attitudes and skills. The conclusion of the study is that the cooperative learning model type make a match with scientific literacy has a positive effect on students' learning competencies in the material of global warming at Payakumbuh 1 Junior High School.